14C DATING OF THE ERLITOU SITE. Issue 4 (17th August 2022) - Zhang, Xuelian; Qiu, Shihua; Cai, Lianzhen; Xu, Hong; Zhao, Haitao; Chen, Guoliang
ABSTRACT: This article outlines the research progress on radiocarbon ( 14 C) dating of the Erlitou site. The Erlitou site, belonging to the Bronze Age, located in Yanshi, Henan province, China, was discovered by archaeologists in 1959 when they investigated the Xia people's remains in the area where the Xia people lived according to the records of ancient documents. Since then, there has been a standing debate about whether the site belongs to the Xia or Shang dynasty. By the mid-1990s, several hundred discussion articles on the issue had been published, but the question was still unresolved. Therefore, evidence from the chronology has attracted a great amount of attention. The dating of the Erlitou site began in the 1970s, and since the Xia-Shang-Zhou Chronology Project began in the mid-1990s, by application of wiggle-matching on the basis of improving the dating accuracy, the date of the Erlitou site has gradually become clear, which provides a basis for the archaeological research on the Xia and Shang dynasties.